Effects of alternating wet and dry irrigation regimes on rice growth and physiology characteristics in southeast China - Zhou, Rui; Yan, Haofang; Zhang, Chuan; Zhu, Xingye; Wang, Guoqing; He, Bin; Disasa, Kinda Negessa; Lakhiar, Imran Ali; Xue, Run; Zhou, Yudong; Wang, Biyu; Li, Jun; et al. (Paddy and water environment, 2025)
Alternative wet and dry irrigation (AWD) has been widely used for rice plants in many countries. Determining the appropriate irrigation amount for different growth stages is of great significance for balancing irrigation water use efficiency ( WUE ) and yield. Five irrigation regimes: continuous flooding irrigation as control group (CK), AWD in early tillering and jointing stage (CW1), AWD in whole growth stage (CW2), slightly controlled irrigation with a minimum moisture soil content in the range 60–85% θ s (CW3) and severely controlled irrigation with minimum soil moisture content in the range of 50–60% θ s (CW4), were applied in this study for rice fields in southeast China. The growth index, root morphology, physiological characteristics, chlorophyll fluorescence parameters, soil physicochemical properties, and rice yield were measured under the five irrigation regimes. The results showed that different irrigation treatments had no significant effects on plant height at all growth stages of rice plants but had greater effects on LAI at the heading and milking stages. In comparison with CK, the LAI decreased by 6.72% under the CW4 treatment. Additionally, the total root length, root volume, and root surface area increased by 21.7%, 24.2%, and 25.4%, respectively, in the CW1 treatment compared with the CK treatment. The maximum transpiration rates ( T r ) of the CW1 treatment at different growth stages were 40.58%, 39.92%, and 38.76% higher than those of the CW2, CW3, and CW4 treatments, respectively. The amount of irrigation had a significant influence on the T r of rice. The influence of the different irrigation regimes on the maximum quantum efficiency ( F v /F m ) of rice at the milking stage was more significant than that at the heading stage. At 13:00 of heading and milk maturity, the F v /F m of CW1 increased by 0.073 and 0.097 compared to that of CW4, respectively, and increased by 0.015–0.055 and 0.055–0.080 for the rest of the day. The results also showed that, compared with CK, the CW1 and CW2 treatments reduced soil bulk density and increased soil porosity, which were conducive to crop root growth, and the CW1 treatment significantly reduced the soil (10–40 cm) NO 3 − N content. Compared with CK, CW1 treatment increased WUE by 67.8% and yield by 4.22%, whereas the WUE of CW2, CW3, and CW4 treatments increased significantly by 127.2%, 156.5%, and 246.2%, respectively, but the yield decreased by 6.4%, 17.5%, and 26.3%, respectively. It was concluded that AWD at the early tillering joint stage (CW1) can enhance rice yield and improve the growth index and physiological characteristics of rice at each growth stage compared to CK. This may be attributed to the greater soil porosity and promotion of better crop root growth associated with CW1, making it a suitable AWD irrigation regime for rice cultivation in southeast China.